Prediction of Early Treatment Response in Multiple Myeloma Using MY-RADS Total Burden Score, ADC, and Fat Fraction From Whole-Body MRI: Impact of Anemia on Predictive Performance - Dong, Huazheng; Huang, Wenyang; Ji, Xiaodong; Huang, Lixiang; Zou, Dehui; Hao, Mu; Deng, Shuhui; Shen, Zhiwei; Lu, Xiudi; Wang, Jian; Song, Zhiyi; Zhang, Xuening; et al. (American journal of roentgenology (1976), 2022)
. The recently released Myeloma Response Assessment and Diagnosis System (MY-RADS) for multiple myeloma (MM) evaluation using whole-body MRI (WB-MRI) describes the total burden score. However, assessment is confounded by red bone marrow hyperplasia in anemia. . The purpose of this study is to assess the utility of the MY-RADS total burden score, ADC, and fat fraction (FF) from WB-MRI in predicting early treatment response in patients with newly diagnosed MM and to compare the utility of these measures between patients with and without anemia. . This retrospective study included 56 patients (40 men, 16 women; mean age, 57.4 ± 9.6 [SD] years) with newly diagnosed MM who underwent baseline WB-MRI including DWI and modified Dixon sequences. Two radiologists recorded total burden score using MY-RADS and measured the ADC and FF of diffuse and focal disease sites. Mean values across sites were derived. Interobserver agreement was evaluated, and the mean assessments of the readers were used for further analyses. Presence of deep response after four cycles of induction chemotherapy was recorded. Patients were classified as having anemia if their hemoglobin level was less than 100 g/L. The utility of WBMRI parameters in predicting deep response was assessed. . A total of 24 of 56 patients showed deep response, and 25 of 56 patients had anemia. Interobserver agreement, which was expressed using intraclass correlation coefficients, ranged from 0.95 to 0.99. Among patients without anemia, those with deep response compared with those without deep response had a lower total burden score (9.0 vs 18.0), a lower ADC (0.79 × 10 mm /s vs 1.08 × 10 mm /s), and a higher FF (0.21 vs 0.10) (all < .001). The combination of these three parameters (optimal cutoffs: ≤ 15 for total burden score, ≤ 0.84 × 10 mm /s for ADC, and > 0.16 for FF) achieved sensitivity of 93.8%, specificity of 93.3%, and accuracy of 93.5% for predicting deep response. In patients with anemia, none of the three parameters were significantly different between patients with and without deep response (all > .05), and the combination of parameters achieved sensitivity of 56.3%, specificity of 100.0%, and accuracy of 72.0%. . Low total burden score, low ADC, and high FF from WB-MRI may predict deep response in patients with MM, although only among those without anemia. . WB-MRI findings may help guide determination of prognosis and initial treatment selection in MM.